2005
DOI: 10.1108/09600030510594549
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the influence of multiple expiration dates on revenue generation in the supply chain

Abstract: Purpose -Inventory control models for perishable products have primarily used a FIFO issuing policy with the objective of minimizing the number of outdated units. This paper aims to develop a model to evaluate an issuing policy for a single product with a fixed shelf life in single echelon inventory system. The issuing policy considers the remaining shelf life of the in-stock inventory and the expected time that the product will spend in inventory as the decision driver. Design/methodology/approach -The model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The label information and expiry dates must also be easy to read and must position the customer to make efficient purchases. In a recent study, Huq et al 6 found that perishability is an important piece of information to consumers, as it refers to the physical deterioration of a product, implying either a fixed or random product lifetime, after which the product unit has no value to the consumer. A study by the Australian Government Department of Health and Ageing 7 confirms that consumers not only check for expiry dates, but also seek more extensive information from labels (eg directions, product description and composition) to make informed and healthy choices.…”
Section: Methodsmentioning
confidence: 99%
“…The label information and expiry dates must also be easy to read and must position the customer to make efficient purchases. In a recent study, Huq et al 6 found that perishability is an important piece of information to consumers, as it refers to the physical deterioration of a product, implying either a fixed or random product lifetime, after which the product unit has no value to the consumer. A study by the Australian Government Department of Health and Ageing 7 confirms that consumers not only check for expiry dates, but also seek more extensive information from labels (eg directions, product description and composition) to make informed and healthy choices.…”
Section: Methodsmentioning
confidence: 99%
“…Among existing investigations is the work of Huq et al (2005) who develop a model that evaluates a new policy for a single perishable product with a fixed shelf life in a single echelon inventory system. The policy considers the remaining shelf life of products inventory instead of the first in first out (FIFO) approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second type of studies, although emerging, considers the impact of having information on products' real freshness in order to improve inventory management. Among existing investigations is the work of Huq et al (2005) who develop a model that evaluates a new policy for a single perishable product with a fixed shelf life in a single echelon inventory system. The policy considers the remaining shelf life of products inventory instead of the first in first out (FIFO) approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The label information and expiry dates must also be easy to read and must position the customer to make efficient purchases. In a recent study, Huq et al (2005) found that perishability is an important piece of information to consumers as it refers to the physical deterioration of a product, implying either a fixed or random product lifetime, after which the product unit has no value to the consumer. A study by the Australian Government Department of Health and Ageing (2003) confirms that consumers are not only sighting expiry dates, but are indeed seeking more extensive information from labels, (directions, product description and composition) to make informed and healthy choices.…”
Section: Literature Reviewmentioning
confidence: 99%